Analisis Penyusunan Anggaran dalam Mendukung Efektivitas Program Kerja: Studi Pada Kanwil Kementerian Hukum Jawa Barat - Vanya Alliqa Hendra; Herry Sutanto (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Budget preparation is a strategic instrument for supporting the effectiveness of work program implementation in public sector organizations. This study aims to analyze the budget preparation process in supporting the effectiveness of work programs at the Regional Office of the Ministry of Law of West Java. The study employed a qualitative approach using a library research method by analyzing books, scientific articles, regulations, and official documents related to public sector budgeting. Data were analyzed using content analysis and thematic synthesis to identify the relationship between the budget preparation process, performance-based budgeting, and work program effectiveness. The findings indicate that budget preparation based on the principles of performance-based budgeting and value for money supports the achievement of organizational objectives through more effective, efficient, transparent, and accountable resource allocation. Strengthening coordination, improving the competence of government personnel, optimizing the use of information technology, and conducting continuous evaluation are essential factors in enhancing the quality of budget preparation and the effectiveness of work programs.